2021
DOI: 10.1002/ange.202100806
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical Prebiotic Peptide Bond Formation**

Abstract: The presence of amino acids on the prebiotic Earth, either stemming from endogenous chemical routes or delivered by meteorites, is consensually accepted. In contrast, prebiotically plausible pathways to achieve peptides from unactivated amino acids are still unclear since most oligomerization approaches rely on thermodynamically disfavored reactions in solution. Alternative hypotheses such as the prebiotic impact scenario postulate that the mechanical impacts from meteorites and geochemical phenomena played an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 92 publications
(139 reference statements)
0
8
0
Order By: Relevance
“…Thus, the abiotic synthesis of peptides is an important step in the prebi-otic chemistry that led to the emergence of life on the primitive Earth. Various scenarios have been suggested on the synthesis of peptides on the prebiotic Earth, which include synthesis in hydrothermal vents and dehydrating condition under dry and wet cycles [54]; synthesis triggers by activating agents [55,56]; presence of mineral catalysis [57,58], high energy protons and UV irradiation [59,60]; volcanic environment [37] and mechanochemical synthesis [50]. However, long polypeptide chains, as found in the present investigation, has not been reported before.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…Thus, the abiotic synthesis of peptides is an important step in the prebi-otic chemistry that led to the emergence of life on the primitive Earth. Various scenarios have been suggested on the synthesis of peptides on the prebiotic Earth, which include synthesis in hydrothermal vents and dehydrating condition under dry and wet cycles [54]; synthesis triggers by activating agents [55,56]; presence of mineral catalysis [57,58], high energy protons and UV irradiation [59,60]; volcanic environment [37] and mechanochemical synthesis [50]. However, long polypeptide chains, as found in the present investigation, has not been reported before.…”
Section: Discussionmentioning
confidence: 43%
“…Long polypeptide chains up to sequence of twelve amino acids as observed in case of glycine is remarkable and has never been reported before. Previous studies have reported shorter peptides using gas gun experiments [31,32] and ball milling techniques [50] simulating extraterrestrial impacts.…”
Section: Mass Spectrometry Of Ejecta Materialsmentioning
confidence: 99%
“…[22][23][24][25][26][27] Catalytic amide bond formation [28][29][30][31][32][33][34][35][36][37] by direct condensation of non-activated carboxylic acids and amines is among the most relevant reactions enabled by Zr catalysts, [38][39][40][41] given their favorable atom economy compared to the amide coupling reagents, [42][43][44][45][46][47][48] and the ready availability of carboxylic acid and amine substrates. [22][23][24][49][50][51][52] However, recent promising advances in metal catalysts are still challenged by the catalyst overall stability, and its tolerance to the water formed as the reaction by-product. 23,24,[53][54][55][56] On the other hand, we have recently discovered metal oxo cluster based catalysts, namely Zr/Hf-polyoxometalates and Zr-based MOFs, exhibit an unusual robustness, allowing reactions to be conducted under 'open-flask' conditions, without any special measures, additives or water scavenging.…”
Section: Introductionmentioning
confidence: 99%
“…In most RNA-centric models, the ribosome and protein synthesis are late addenda to proto-biology. An alternative class of models proposes instead that a creative stage of chemical evolution (Yu et al 2016 ; Frenkel-Pinter et al 2019 , 2020 ; Stolar et al 2021 ) merged smoothly with Darwinian processes. In some of these models the ribosome was an early foundation to proto-biology; multiple types of biopolymers, some primarily informational and others primarily catalytic, arose in concert via co-evolution (Lanier et al 2017 ; Frenkel-Pinter et al 2020 ).…”
Section: Summary and Future Prospectsmentioning
confidence: 99%